Statistical analysis of gender pay gap in modern-day Russia - I. I. Eliseeva; M. Р. Dekina (Статистика и экономика, 2019)
Purpose of the study. The study of gender disparity remains relevant for all countries, including the Russian Federation. The study of disparity in quantitative terms: the income distribution, in which the main source – wages, is of particular importance. In the analysis of the gender pay gap, the main factors are such characteristics as the level of education, work status, district, age and the period of the employee’s service. The purpose of this article is a statistical assessment of gender differentiation of wages in Russia based on empirical data and aggregated data from the Federal State Statistics Service. Particular attention is paid to the econometric approach to gender differences in wages.  Materials and methods. As the main sources of information were data from the Federal State Statistics Service. In addition as the empirical base of the study, the data from the 27th wave of the Russian Longitudinal Monitoring Survey (RLMS) – Higher School of Economics were used. The study is based on a modified Mincer`s type equation. Models of the logarithm of wages for all employees, as well as separately for men and women, were developed. To clarify the range of factors, affecting wage differences, models were developed with either the age of the employees or the period of their service. In addition, the factor “socio-professional group” was included, due to the presence of marked gender differentiation among occupational groups. On the base of the constructed models, the gender difference in wages was decomposed.  Results. The results allowed quantifying the impact of gender on wages, as well as assessing the impact of various factors separately for male and female. It was found a stronger influence of education on the women wages, which indicates, on the one hand, the intellectual advantages of women, and on the other hand, indicates the difficulty of obtaining decent earnings for women with low education. The factor of residence is more affected for men. Decomposition of gender difference in wages allowed us to establish the continued existence of gender inequality in the Russian Federation, ceteris paribus.  Conclusion. The study of gender wage differentiation remains an important element in the analysis of both wage differentiation in general and gender disparity. The results of the analysis confirmed the persistence of gender differentiation wages in Russia at present. In the future, it is necessary to expand the analysis of gender differentiation of wages with the following characteristics: additional education, health, marital status, differences in the education of husband and wife, and the presence of preschool children.